PELATIHAN LARI INTERVAL 8 X 100 M, LEBIH BAIK DARI PELATIHAN LARI INTERVAL 4 X 200 M DAN 2 X 400 M DALAM MENINGKATKAN KECEPATAN LARI 400 M SISWA SMK NEGERI 5 DENPASAR - Ni Ketut Ayu Juliasih (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2013)
This study aimed to assess the increase of speed of the 400 m running obtained from a training of interval running of 800 m distance programmed in three types of models and to find out which one of the three training models gave the greatest improvement of speed. The three models of training were interval sprint of 8 x 100 meters, 4 x 200 meters, and 2 x 400 meters, carried out in 4 sets, 3 times a week, for a 6 week duration. This study was an experimental study using the Randomized Pre and Post Test Group Design. The study subjects comprised 24 students of SMK Negeri 5 Denpasar, who were divided into 3 groups of 8 students each. Group 1 was assigned to 8 x 100 m run, group 2 to 4 x 200 m run, and group 3 to 2 x 400 m run training, respectively. The data were analyzed accordingly with the test of T-Paired, One-way Anova, and LSD. The result of the T-Paired test on each group before anf after training showed a significant mprovement of the running speed (p<0.05). Therefore, indicating an improvement of 400 m running speed was achieved in each group. The One-Way Anova test showed a significant difference was found among the three groups in the increase of running speed obtained after training (p<0.05). The LSD test showed there was a significant difference of the increase of running speed between Group 1 and 2, and between Group 1 and 3 (p<0.05). There was no significant difference of speed found between Group 2 and 3 (p>0.05). Therefore, the training of interval 8 x 100 meters run was more effective in increasing the running speed as compared with interval 4 x 200 meters and 2 x 400 meters run, respectively, among the students of SMK 5 Denpasar.